Field research 2013 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Includes research reports from these locations: East Central Kansas Experiment Field. Kansas River Valley Experiment Field, and Kansas State University Department of Agronomy.
Keywords: Kansas; Agriculture; Crops; Weed control; Disease control; Fertilizer; Irrigation